2017
DOI: 10.1016/j.psep.2017.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis and UV/H 2 O 2 of diclofenac, sulfamethoxazole, carbamazepine, and trimethoprim: Identification of their major degradation products by ESI–LC–MS and assessment of the toxicity of reaction mixtures

Abstract: The photolysis of diclofenac (DCF), sulfamethoxazole (SMX), carbamazepine (CBZ), and trimethoprim (TMP) was investigated using a low-pressure (LP) mercury ultraviolet (UV) lamp (254nm) and a combination of UV with hydrogen peroxide (H 2 O 2). For each experiment, 5mg/L of each pharmaceutical was prepared in pure water and individually degraded by either UV alone or UV/H 2 O 2. DCF and SMX were highly susceptible to UV treatment and completely degraded to below their LC-MS detection limit (1μg/L) after only 8mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(67 citation statements)
references
References 56 publications
2
53
0
1
Order By: Relevance
“…For instance, adding a single dose of H 2 O 2 (5-15%) to UV photolysis process resulted in an enhanced CBZ removal of 60-75% [225,226]. In another study, H 2 O 2 -concentration dependent increase in CBZ removal by UV/H 2 O 2 process was reported, and 99% removal was achieved at an initial H 2 O 2 concentration of 120 mg/L [220]. CBZ removal can improve with increasing H 2 O 2 concentration but it will reach a plateau beyond a threshold H 2 O 2 concentration [220].…”
Section: Cbz Degradation By Advanced Oxidation Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, adding a single dose of H 2 O 2 (5-15%) to UV photolysis process resulted in an enhanced CBZ removal of 60-75% [225,226]. In another study, H 2 O 2 -concentration dependent increase in CBZ removal by UV/H 2 O 2 process was reported, and 99% removal was achieved at an initial H 2 O 2 concentration of 120 mg/L [220]. CBZ removal can improve with increasing H 2 O 2 concentration but it will reach a plateau beyond a threshold H 2 O 2 concentration [220].…”
Section: Cbz Degradation By Advanced Oxidation Processesmentioning
confidence: 99%
“…Although UV photlysis alone has been observed to be ineffective for CBZ removal (0-20%) in a number of studies [220,231], removal can be significantly improved by adding H 2 O 2 or a photocatalyst such as TiO 2 [214,220]. For instance, adding a single dose of H 2 O 2 (5-15%) to UV photolysis process resulted in an enhanced CBZ removal of 60-75% [225,226].…”
Section: Cbz Degradation By Advanced Oxidation Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ternes et al [197] reported almost complete removal (>99%) of CBZ (35-1000 ng/L) during ozonation process at an initial dose of 0.5 mg/L. Although UV photlysis alone has been observed to be ineffective for CBZ removal (0-20%) in a number of studies [220,231], removal can be significantly improved by adding H 2 O 2 or a photocatalyst such as TiO 2 [214,220]. For instance, adding a single dose of H 2 O 2 (5-15%) to UV photolysis process resulted in an enhanced CBZ removal of 60-75% [225,226].…”
Section: Cbz Degradation By Advanced Oxidation Processesmentioning
confidence: 99%
“…The main goal of the present work was to compare the outcomes of UVC photolysis and UV/H 2 O 2 in the context of TPs analysis and toxicity assessment. As the previous efforts focused primarily on the photolysis process [12,13], the studies on the application of UV/H 2 O 2 towards diclofenac degradation are still rather scarce [1]. Therefore, there is a need for broad-scope experimental work aimed at providing a comparative perspective on the diclofenac-related outcomes of photolysis and UV/H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%